Peran Transformational Leadership dalam Memoderasi Pengaruh Quality of Worklife dan Workplace Spirituality terhadap Kinerja Pegawai - Wikarno Wikarno (CV. ULIL ALBAB CORP, 2025)
This study examines the influence of quality of worklife and workplace spirituality on employee performance, as well as the role of transformational leadership as a moderating variable at the Bank Indonesia Representative Office in East Kalimantan Province. The research employs a census method with 48 respondents and is analyzed using SmartPLS 4.0. The results show that workplace spirituality has a positive and significant effect on employee performance. This concept, which includes a sense of community, value alignment, contribution, workplace serenity, and opportunities for spiritual life, effectively enhances employee performance. In contrast, quality of worklife, encompassing fair compensation, a safe work environment, capacity development, and social relationships, does not influence employee performance, highlighting the need for more effective quality of worklife development. Moreover, transformational leadership does not strengthen the relationship between these variables and employee performance. In a highly structural and formal organizational context, where spiritual values are well-internalized, transformational leadership—characterized by intellectual stimulation, individual consideration, inspirational motivation, and idealized influence—fails to significantly enhance performance. This study emphasizes the critical role of workplace spirituality in improving employee performance, surpassing the impacts of quality of worklife and transformational leadership.